2017
DOI: 10.3938/jkps.70.339
|View full text |Cite
|
Sign up to set email alerts
|

Eigen solutions, Shannon entropy and fisher information under the Eckart Manning Rosen potential model

Abstract: We solved the Schr¨ odinger equation with a certain approximation to the centrifugal term for an arbitrary angular momentum state with the Eckart Manning Rosen potential. The bound-state energy eigenvalues and the corresponding wave functions have been approximately obtained using the parametric Nikiforov Uvarov method. The solutions of the Schr¨ odinger equation for the Eckart potential, Manning Rosen potential, and Hulth´ en potential have been obtained using a certain transformation. The concepts of the Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Recent studies have focused on the combination of, at least, two potentials. The essence of combining two or more physical potential models is to take into account more physical phenomena into existing investigations of molecular physics [81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused on the combination of, at least, two potentials. The essence of combining two or more physical potential models is to take into account more physical phenomena into existing investigations of molecular physics [81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%
“…The essence of joining at least two physical potential models is to take into account more physical application and comparative analysis to existing investigations of molecular physics [81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%
“…The analytical solution of the Schrödinger equation with ℓ = 0 and ℓ ≠ 0 for some potentials has been addressed by many researchers in non-relativistic and relativistic quantum mechanics for bound states (Durmus and Yasuk, 2007;Edet et al, 2020d;2021b;Louis et al, 2018a;. Some of these potentials include Deng-Fan potential (Falaye et al, 2015), Hyperbolic potential (Onate et al, 2018b), Eckart potential (Onate et al, 2017), generalized trigonometric Pöschl-Teller potential (Edet et al, 2020e), and screened Kratzer Potential (Ikot et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several authors have reported the computation for Fisher information for different physical potential models. Among the works reported are: Fisher information and variance with Frost‐Musulin potential, Fisher information‐based uncertainty relation, Cramer‐Rao inequality and kinetic energy for the D‐dimensional central problem, information and complexity measures for the ring‐shaped modified Kratzer potential, Fisher information for position‐dependent mass Schrödinger system, quantum information‐theoretic measures for the static screened Coulomb potential, Fisher information of a single‐particle system with a central potential, Fisher information and complexity measure of generalized Morse potential model, Eigen solutions, Shannon entropy and Fisher information under Eckart Manning‐Rosen potential model, Eigensolution techniques, their applications and Fisher's information entropy of the Tietz‐Wei diatomic molecular model, Fisher information in confined hydrogen‐like ions, Fisher information in confined isotropic harmonic oscillator, Fisher information and complexity measure of Generalized Morse potential model, Shannon and Fisher entropy measures for a parity‐restricted harmonic oscillator, radial position‐momentum uncertainties for the infinite circular well and Fisher entropy, quantum information measures of infinite spherical well . In this study, the authors aimed at investigating the solutions of the radial Schrödinger equation and Fisher information confined in a potential family which is proposed in the course of this study.…”
Section: Introductionmentioning
confidence: 99%